Social engineering as a method of information and telecommunication systems intelligence - Бурячок, Володимир Леонідович; Корченко, Олександр Григорович; Бурячок, Лідія Володимирівна (Ukrainian Information Security Research Journal, 2012)
The rapid technological development of information society that circulates, accumulates and is processed in information and cyberspace leads to the increase of information. This process requires the development of new (improving existing) strategies and methods for searching and collecting information in an open, relatively open closed electronic sources. The solution of these tasks is possible within such a promising activity, as information and telecommunication systems (ІТS) intelligence, integrated research that neither domestic nor foreign specialists until this time wasn’t conducted. On the basis of the analysis of open sources there were revealed the main aspects, features, techniques and methods of ITS intelligence and determined that it would be recognized as the most effective means of identifying, preventing, countering and dealing with a variety of cyber intrusions and threats. The most effective and powerful way of ITS intelligence in the nearest futures will definitely stay the cyber intelligence, is designed to search and collect information, especially in the Internet, and the most effective is a method of social engineering designed to organize an access to the most protected information resources.